Author Correction: Aggravation of acute kidney injury by mPGES-2 down regulation is associated with autophagy inhibition and enhanced apoptosis. Issue 1 (December 2018) - Li, Ting; Liu, Ying; Zhao, Jie; Miao, Shuying; Xu, Yunfei; Liu, Ke; Liu, Meidong; Wang, Guiliang; Xiao, Xianzhong
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.